Insulation resistance in relation to distribution of backsheet types in strings and inverters - Buerhop-Lutz, Claudia; Pickel, Tobias; Stroyuk, Oleksandr; Hauch, Jens; Peters, Ian Marius (Solar Energy Materials and Solar Cells, 2022)
Polymers are essential for long-term green energy production by photovoltaics (PV). We created a unique dataset that links electrical performance data of 28,030 PV modules, combined into 1295 strings and 423 inverters with the identity of the backsheet (BS) materials of each of the tested modules. This dataset gives an insight into BS-versatility and resulting impact on the insulation resistance of strings and inverters. The BSs were analyzed using near infrared absorption spectroscopy (NIRA) plus visual inspection in the field. The insulation resistance (Riso) of selected modules and strings was measured on-site. Furthermore, reported ground impedance (GI) values were evaluated with respect to an inverter-specific threshold below which the inverters do not start operation. We differentiated seven BS-types, the three most frequent being polyamide (PA), fluorinated coating (FC), and polyvinylidene fluoride (PVDF). Although modules with PA show often BS cracking, the insulation resistance was above the threshold. Similar, the GI of inverters with modules with PVDF-BSs was high. Modules with FC-BSs feature generally low Riso–values on module-, string-, and on inverter level. Evaluating historic data reveals an increase in frequency of GI-values below the threshold for inverters connected to modules with exclusively FC-BSs. While inverters with modules having PA- or PVDF-BSs function as expected, inverters with modules having FC-BSs require maintenance to keep power yield on an acceptable level. The dataset collected in the present work highlights that the choice of BS-material of PV-modules is essential for reliable operation of PV power stations.
CRIS-Team Scopus Importer:2022-08-12